2011
DOI: 10.1111/j.2044-8287.2010.02014.x
|View full text |Cite
|
Sign up to set email alerts
|

Social influence, intention to smoke, and adolescent smoking behaviour longitudinal relations

Abstract: Results show direct and indirect effects of social influence on behaviour. Descriptive norms are an important variable to operationalize social influence. Peers and parents exert influence on adolescents' intention and behaviour through different processes. The impact of intention on behaviour is not as important as expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
40
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 51 publications
8
40
2
1
Order By: Relevance
“…Also, certain personal factors we found to predict (low refusal self-efficacy) or protect against (health concerns) WP initiation have also been similarly associated with cigarette smoking initiation (Bidstrup et al, 2009; Hiemstra et al, 2011; O’Loughlin et al, 2009; Piko et al, 2005; Scal et al, 2003; Ma et al, 2008; Chang et al, 2006; Tyas and Pederson, 1998). Finally, in line with our findings, studies measuring smoking intention found this domain to be a strong predictor of cigarette initiation (Vitória et al, 2011; Skara et al, 2001; Stanton et al, 2005). …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, certain personal factors we found to predict (low refusal self-efficacy) or protect against (health concerns) WP initiation have also been similarly associated with cigarette smoking initiation (Bidstrup et al, 2009; Hiemstra et al, 2011; O’Loughlin et al, 2009; Piko et al, 2005; Scal et al, 2003; Ma et al, 2008; Chang et al, 2006; Tyas and Pederson, 1998). Finally, in line with our findings, studies measuring smoking intention found this domain to be a strong predictor of cigarette initiation (Vitória et al, 2011; Skara et al, 2001; Stanton et al, 2005). …”
Section: Discussionsupporting
confidence: 91%
“…Although research on risk factors for WP initiation among adolescents is nonexistent, the temporal precedence of many predictors identified here fit with earlier longitudinal studies on adolescent cigarette smoking initiation (O’Loughlin et al, 2009; Miller et al, 2006; Morgenstern et al, 2013; Bidstrup et al, 2009; Hiemstra et al, 2011; Scal et al, 2003; Ma et al, 2008; Vitória et al, 2011; Skara et al, 2001; Stanton et al, 2005; Chang et al, 2006; Fujimoto et al, 2012; Wood et al, 2013; Tyas and Pederson, 1998). Research has frequently shown that predisposing factors such as use of other tobacco products is predictive of cigarette initiation (O’Loughlin et al, 2009; Mzayek et al, 2012).…”
Section: Discussionsupporting
confidence: 77%
“…It is likely that all of these processes are at work. Some previous studies have reported that descriptive norms (perceived behavior of others) rather than injunctive norms (perceived approval of others) are related to adolescents’ smoking (Vitória et al 2011; Mercken et al 2011). In contrast, we found that both were significantly related to adolescents’ smoking in multivariate models, although the association between adolescents’ own smoking and perceived smoking by friends may be somewhat stronger.…”
Section: Discussionmentioning
confidence: 99%
“…These associations have been reported both cross-sectionally (Villanti et al 2011) and longitudinally (Duan, Chou, Andreeva, & Pentz 2009; Bricker et al 2006). Studies further indicate that descriptive norms may be related more closely to adolescents’ smoking intentions and behavior than are injunctive norms (Vitória, Salgueiro, Silva, & de Vries 2011; Mercken, Candel, van Osch, & de Vries 2011). Given the role of normative beliefs in adolescents’ smoking and their potential significance as targets for prevention, it is important to improve our understanding of how they may interact with the broader normative environment.…”
Section: Introductionmentioning
confidence: 99%
“…10 Another important risk of this parental behaviour is the proven influence on the likelihood of children becoming smokers in the future. 11,12 Despite these consequences, the WHO estimates that worldwide about half of the children (700 million) are exposed to SHS, mainly in their own homes. 9,13 Two Portuguese studies revealed that 38% and 41% of the children were daily or occasionally exposed to SHS caused by their parents' smoke.…”
mentioning
confidence: 99%